Criminalistics in veterinary medicine. Class with graduate students - Friedrich, N. O.; Jimenez Lucena, M. A.; Miño, T. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
The Chair of Legislation of the Catholic University of Cordoba, Argentina, in the unit: Veterinary Legal, implemented as an organizational teaching modality: practical classes carried out in the field, on the theme scene of crime scene. The purpose of these classes is to contribute and to obtain competences in academic knowledge related to the forensic sciences and their ethical application in legal causes; instruct the veterinarian to act as an expert in the face of judicial or extrajudicial requirements, incorporate basic legal, legislative concepts; notions of criminology, tanatology, entomology and lesionology; acquire: skills and abilities, intellectual, interpersonal communication, organization and personal management; attitudes, values of development and professional commitment.